2009
DOI: 10.1007/s12529-008-9015-3
|View full text |Cite
|
Sign up to set email alerts
|

Health Behavior and Protective Factors Among School Children in Four African Countries

Abstract: These findings enable health care professionals and researchers designing intervention studies to promote positive health practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
2
27
0
2
Order By: Relevance
“…The findings of the study urges the need for multi-component intervention to reduce pre-teen alcohol use because alcohol use in Africa has been linked to poverty and risky sexual practices, 16,1820 which worsen already dire social and personal conditions. Also, including or amplifying strategies to increase protective factors, such as school attendance, parental or guardian connectedness, peer support at school, and parental supervision 35 are critical in preventing adverse health outcomes among African youth.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study urges the need for multi-component intervention to reduce pre-teen alcohol use because alcohol use in Africa has been linked to poverty and risky sexual practices, 16,1820 which worsen already dire social and personal conditions. Also, including or amplifying strategies to increase protective factors, such as school attendance, parental or guardian connectedness, peer support at school, and parental supervision 35 are critical in preventing adverse health outcomes among African youth.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of physical inactivity is defined as doing none or very little physical activity at work, at home, for transport, or during discretionary time. It has been reported that less than 50% of children and youths from African countries are physically active for at least 60 min a day at least three days a week [9,10]. In Senegal, few studies have investigated the physical activity level among school children or adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of physical inactivity, defined as doing no or very little physical activity at work, at home, for transport or during discretionary time, has been estimated to be 43%–49% in South Africans 15 years of age and older [5], and it has been reported from other African countries that less than 50% of adolescents between 13 and 15 years of age are physically active for at least 60 minutes a day on at least 3 days a week [6]. Objective measures of physical activity in rural-dwelling South African men and women confirmed the significant contribution of ambulatory (walking) activity to overall physical activity in this population [7], and the association between ambulatory activity and adiposity [8] provides more reason for why it is important to understand factors, specific to rural South African adolescents, associated with physical activity.…”
Section: Introductionmentioning
confidence: 99%